Entrepreneurial orientation of Muslim Micro, Small and Medium Enterprises (MSMEs) owners in West Sumatra - Fauziah Taslim; Annisa Lestari Kadiyono (INSPIRA: Indonesian Journal of Psychological Research, 2023)
This study aims to provide an overview of Entrepreneurial Orientation in Muslim’s Micro, Small and Medium Enterprises (MSMEs) in West Sumatera Province who are ranked in the top 10 in the number and growth of national Micro, Small and Medium Enterprises. This research used quantitative approach with random sampling (n = 671). Participant of this study are muslim entrepreneurs from different backgrounds such as genders, education, and residence. Individual Entrepreneurial Orientation (IEO) scale was used as the instrument of measurement. The data analysis used is descriptive statistics and mean comparison. The results of the study found that the majority of Micro, Small and Medium Enterprises in West Sumatera opened business in the culinary field and had a very high Entrepreneurial Orientation. Based on the average per dimension, all dimensions had high scores. The dimension of perseverance has the highest average score (8.52) while the lowest score is owned by the innovativeness dimension (7.98). Based on means comparison, significant differences in entrepreneurial orientation were found based on the categories of gender, age, city origin, and gross profit.